2020
DOI: 10.1002/nau.24378
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder and urgency urinary incontinence in men undergoing artificial urinary sphincter placement

Abstract: Purpose To assess persistent and de novo rates of overactive bladder (OAB) and urgency urinary incontinence (UUI) in patients with incontinence after prostate treatment (IPT) focusing on differences between surgical intervention vs radiation. Methods We performed a retrospective review of 79 patients who underwent primary artificial urinary sphincter (AUS) placement and activation from a single surgeon between February 2012 and November 2017. Four patients with neurogenic bladder were excluded and two with ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The results of the search strategy and the number of records at each stage are presented in Figure 1. A total of 18 studies met the inclusion criteria and were reviewed in our study (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Details of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the search strategy and the number of records at each stage are presented in Figure 1. A total of 18 studies met the inclusion criteria and were reviewed in our study (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Details of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to extract data on the absence of urinary incontinence after AUS placement from eight studies ( 14 , 17 , 18 , 22 , 23 , 25 , 28 , 29 ). Comparing data of 281 patients with a history of RT vs. 489 patients without RT, we noted statistically significant reduced odds of the absence of incontinence in the RT group (OR: 0.35 95% CI: 0.21, 0.59 I 2 = 51% p < 0.0001) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] In contrast, other studies reported that a history of RT was associated with significantly worse outcomes, including continent status and complications after AUS implantation. [9][10][11][12][13] To date, there have been no studies investigating the impact of a history of pelvic RT on LUTS other than UI after AUS implantation.…”
Section: Introductionmentioning
confidence: 99%
“…For those who have symptomatic benign prostatic enlargement, appropriate treatment should be undertaken too. Detrusor overactivity and poorly compliant bladder should be treated adequately before the AUS surgery, 27 , 28 although intravesical botulinum therapy can be administered using flexible cystoscopy in patients with an in‐situ AUS.…”
Section: Main Recommendationsmentioning
confidence: 99%